Microencapsulated curcumin from Curcuma longa modulates diet-induced hypercholesterolemia in Sprague Dawley rats - Ashraf, Humaira; Butt, Masood Sadiq; Iahtisham-Ul-Haq; Nadeem, Muhammad; Aadil, Rana Muhammad; Rusu, Alexandru Vasile; Trif, Monica (Frontiers in Nutrition, 2022)
Hypercholesterolemia is one of the major causes of cardiovascular ailments. The study has been conducted on the hypothesis that hypercholesterolemia can be modulated by microencapsulated curcumin due to its enhanced bioavailability. In this context, curcumin obtained from fresh rhizomes of Curcuma longa by conventional (CSE) and supercritical fluid (SFE) extractions, has been successfully microencapsulated using a mixture of gelatin and maltodextrin. The microencapsulated curcumin CSE & SFE, has been added as supplemented diet and has been resulted in maximum plasma concentration of curcumin at 100 min as 529.31±8.73 & 405.23±7.12 µg/mL, respectively compared to non-encapsulated turmeric powder used as control. During the bio evaluation trial, turmeric powder (3%), microencapsulated curcuminCSE (1%) and microencapsulated curcuminSFE (0.5%) were provided to designate rat groups categorized by normal; N1, N2 and N3 and hypercholesterolemic; H1, H2 and H3 conditions, respectively. The incorporation of microencapsulated curcuminSFE in the supplemented diet caused a reduction in serum cholesterol, low density lipoprotein (LDL) and triglycerides, athrogenic index (AI) and cardiac risk ration (CRR) as 5.42 & 12.81%, 7.25 & 15.42%, 3.17 & 9.38%, 15.38 & 29.28% and 10.98 19.38% in normo- & hypercholesterolemic rat groups. Additionally, high-density lipoprotein (HDL) and anti-atherogenic index (AAI) indicated a significant increase in all treated rat groups. Conclusively, the inclusion of turmeric and curcumin microencapsulates in the dietary module has been proven effective to alleviate hyperlipidemia. Therefore, the present study is proven that curcumin absorption via the gastrointestinal tract and its stability towards metabolization in the body increased via microencapsulation using maltodextrin and gelatin. Microencapsulated curcumin reaches the target site via oral administration because of sufficient gastrointestinal residence period and stability in the digestive tract.